Demands and Material Flow of Recycled Polyethylene Terephthalate (PET) in Indonesia - Evtriyandani; Warmadewanthi IDAA; Pratama Jeesica Hermayanti; Sekuła Paulina Magdalena (BIO Web of Conferences)
It has been a resultant factor behind population growth leading up to increased consumption and demand for fast-moving consumer goods. Higher consumption fosters industrial growth but simultaneously increases plastic waste generation, one of which is polyethylene Terephthalate (PET). PET is widely applied as a packaging material due to its recyclable nature and affordability. Recycled PET functions as a substitute for raw materials produced directly from petroleum. This research aims to analyze the current PET recycling rates to substitute the demand for virgin PET materials in Indonesia. The material flow analysis in this study used the STAN 2.7 application with data sources from the literature and the Central Bureau of Statistics of the Republic of Indonesia. From this research, the consumption of PET in Indonesia is about 1 million tons annually. The bottled water industry is the major consuming of around 300,000 tonnes annually. Recycled PET can provide only 17% of the plastic PET plastic demand. Half of the PET is provided by imported virgin materials. Public-private-government collaboration considers promoting recycling and increasing proper waste management. The findings could act as evaluative tools indicating that the recycling rate can be enhanced to reduce the dependence on virgin material imports.